Identification of Genes Present Specifically in a Virulent Strain of Klebsiella pneumoniae - Lai, Yi-Chyi (American Society for Microbiology, 2000)
Klebsiella pneumoniae is a common cause of septicemia and urinary tract infections. The PCR-supported genomic subtractive hybridization was employed to identify genes specifically present in a virulent strain of K. pneumoniae. Analysis of 25 subtracted DNA clones has revealed 19 distinct nucleotide sequences. Two of the sequences were found to be the genes encoding the transposase of Tn3926 and a capsule polysaccharide exporting enzyme. Three sequences displayed moderate homology with bvgAS, which encodes a two-component signal transduction system in Bordetella pertussis. The rest of the sequences did not exhibit homology with any known genes. The distribution of these novel sequences varied greatly in K. pneumoniae clinical isolates, reflecting the heterogeneous nature of the K. pneumoniae population.